Contact dermatitis to acrylates and secondary nail fungal infection in 22 year old female patient – a case report - Gruszczyńska, Michalina; Jarzemski, Adam; Kolossa, Agnieszka; Porzych, Rafał; Marzyńska, Dorota; Depczyńska, Michalina; Gruszka, Beata; Gruszka, Alicja (Journal of Education, Health and Sport, 2023)
Contact dermatitis is an inflammatory skin disease resulting from repeated contact with allergens or irritants. Prevalence of adverse reactions to acrylates monomers is still rising due to their wide use in medical and cosmetics industry. The nail symptoms, including e.g. onycholysis, hyperkeratosis or nail plate discoloration can be indicative of different diagnoses like psoriasis, mycobacterial infections or contact dermatitis. Diagnosis is not always obvious, as exemplified by the patient’s history. The aim of the study was to describe a case of contact dermatitis to acrylates associated with secondary fungal nail infection. Moreover article reviews the pathogenesis, clinical manifestation, diagnosis and treatment methods of contact dermatitis induced by acrylates.